A SEM-ANN analysis to examine sustainable performance in SMEs: The moderating role of transformational leadership - Hidayat-ur-Rehman, Imdadullah; Alsolamy, Majed (Journal of open innovation, 2023)
The central aim of this research study is to investigate the interconnections and dynamics within small and medium-sized enterprises (SMEs) by examining Fintech adoption, competitiveness, circular economy practices, transformational leadership, and sustainable performance. The study's theoretical framework is grounded in the Practice-Based View, integrating Fintech adoption, competitiveness, circular economy practices, transformational leadership, and sustainable performance into the proposed model. To validate this model, the research employs the SEM-ANN analysis method. The study focuses on workers within SMEs in Pakistan, with a sample of 473 participants collected using a simple random sampling technique and 442 samples were deemed suitable for analysis. Preliminary data examination and hypothesis testing were conducted using Smart-PLS 4.0 and SPSS-23. A two-fold SEM-ANN approach was employed to validate the study's proposed model. The research findings indicate a direct and significant impact of Fintech adoption and transformational leadership on the sustainable performance of SMEs. Circular economy practices and competitiveness play vital intermediary roles, connecting Fintech adoption and sustainable performance. Furthermore, transformational leadership acts to moderate the relationships between Fintech adoption and both circular economy practices and competitiveness. The ANN approach complements the SEM analysis, providing additional insights and expanding our understanding of the subject. This study illuminates the interplay between Fintech, circular economy practices, and transformational leadership in enhancing SMEs' competitiveness and sustainable performance. It underscores the pivotal role of integrating Fintech and sustainable practices for SMEs and provides insightful directives for policymakers and scholars aiming to bolster SMEs in a competitive business environment.